CORROSION OF METALS AND ITS IMPACT ON THE ENVIRONMENT - Utayeva Sitora Malik qizi; Bozorova Gulzoda Bahrom qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information on the adverse effects of metal corrosion control, and its metallurgical effects, environmental and metallurgical effects, environmental and activators and inhibitors.